Driven by difference : how great companies fuel innovation through diversity - Livermore, David A., 1967- (AMACOM/American Management Association, 2016)
Today's workforce is more diverse than ever before. But despite new perspectives and talents, the promise of increased innovation rarely materializes. Studies show that diverse teams are more creative than homogenous ones, but only when they are managed effectively. The secret is to minimize conflict while maximizing the informational diversity found in varied values and experiences. To do this, both leaders and team members need a high level of cultural intelligence, or CQ. Drawing on success stories from Google, Alibaba, Novartis, and other groundbreaking companies, this book identifies the management practices necessary to guide multicultural teams to innovation, including how to: create an optimal environment; build trust; fuse differing perspectives; align goals and expectations; gnerate fresh ideas; consider various audiences when selecting and selling an idea; design and test for different users. --